Lou Martyn, Paul, and Judaism - Marcus, Joel (Journal for the study of Paul and his letters, 2017)
J. Louis Martyn was not anti-Judaic but a lover of Jews and Judaism. But his passion for Paul, especially for Galatians, transcended his love for Judaism and may have caused him to downplay some of the difficulties in that letter. This article focuses on Martyn's exegesis of the Sarah/Hagar allegory in Gal 4:21-5:1, which interprets the opposition not as Christianity versus Judaism but as the Torah-free Christian mission to Gentiles versus the Torah-observant mission—an interpretation that this article finds indefensible. The article concludes with some reflections on Martyn's attitude toward Rom 9-11.